SARS-CoV-2 Infection and Incidence of Mucormycosis - Marghoob, Mohsina; Saeed, Umar; Piracha, Zahra Zahid; Shafiq, Haiqa; Fatima, Noor; Sarfraz, Nimra; Farooq, Noor; Uppal, Rizwan (Archives of Clinical and Biomedical Research, 2022)
With COVID 19 becoming a most important worldwide cause of concern, it is significant to comprehend the various manifestations of the disease to fully accomplish it. No country is untouched by the plague of this new disease which was first reported from Wuhan, China in December 2019. It is an infectious disease caused by novel coronavirus i-e; SARS-CoV-2. The rapid spread of this disease as well as the illness and mortality associated with this disease has led to unprecedented research into the various aspects of this disease. While respiratory catalogs are the most predominant feature of this disease, with time it has been initiate that the virus can include almost any organ in the human body. Covid-19 has overcome human wellbeing worldwide while also vigorously affecting the worldwide economy. SARS-CoV-2 has influenced more than 220 nations and domains, with roughly 4176,185 deaths so far across the globe. Recently, Mucormycosis made serious disarray in India during the second wave (among April and June 2021) of the tragical COVID-19 upsurge by its startling and severe overflow with up to half the death rate. Mucormycosis is a deadly parasitic infection brought about by a kind of uncommon yet deft contagious microorganism called mucormycetes. While the specific reason for its sharp ascent out of nowhere and explicitly during the second wave stays disputable, it has been noticed that individuals who are diabetic and have recuperated from COVID-19 disease are more inclined to Mucormycosis. In this review, we will briefly discuss the relation between COVID-19 and Mucormycosis.